Scientific Mapping Research on the Integration of the PjBL Model and Sustainable Development: A Bibliometric Analysis - Cindy Fatika Jeansky Tasilipet; Asrizal Asrizal; Harman Amir; Fauziah Ulmi; Azifa Feziyasti (Universitas Negeri Padang, 2026)
The integration of Project-Based Learning (PjBL) and Education for Sustainable Development (ESD) has become an increasingly studied learning approach because it supports the development of 21st-century competencies and sustainability. This study aims to analyze trends in publications, subject area, country distribution, network visualization, overlay visualization, and density visualization. Research themes relate to the integration between Pjbl and END during the 2015-2025 period. The method used was bibliometric analysis utilizing articles indexed in the Scopus database. The analysis was conducted using Bibliometric and VOSviewer through the mapping of publication trends, author collaborations, keyword co-occurrence, and the evolution of research themes. The results show that publications on the integration of PjBL and ESD have increased significantly, with a focus on active learning, sustainability competencies, critical thinking skills, and the achievement of the Sustainable Development Goals (SDGs). This study provides an overview of the direction of PjBL and ESD research and serves as a reference for researchers and education practitioners in developing learning innovations oriented toward sustainable development.